"To whom did I tell that information?": Relationship between destination memory and theory of mind in traumatic brain injury. Issue 1 (2nd January 2021) - Wilu Wilu, Amina; Allain, Philippe; Moustafa, Ahmed A.; El Haj, Mohamad
Abstract: Traumatic Brain Injury (TBI) has been widely associated with impairment of social cognition. We therefore investigated the relationship between the ability to infer and predict other's mental states (i.e., Theory of Mind, ToM) and the ability to remember to whom one has sent information (i.e., destination memory). We invited patients with TBI and control subjects, on a destination memory task, to tell proverbs to pictures of celebrities, so as to remember to which celebrity they had previously told the proverbs. Participants also performed affective (i.e., Reading the Mind in the Eyes) and cognitive (i.e., the false belief) tests of ToM. Results demonstrated lower destination memory, affective, and cognitive ToM performance in TBI patients than in control subjects. Critically, analysis demonstrated significant positive correlations between destination memory and first order and second cognitive order ToM in patients with TBI, but no significant correlations between destination memory and affective ToM in these patients. Our results demonstrate a relationship between difficulties of TBI patients to infer and predict cognitive states of interlocutors and difficulties to remember to which interlocutor information has been told.